Grundtvigs symbolverden. Af Helge Toldberg - Thomsen, Ejnar (Grundtvig-studier, 1952)
Helge Toldberg: Grundtvigs symbolverden (Grundtvig s Universe of Symbols), Skrifter udgivet af Grundtvig-Selskabet II. Copenhagen, 1950. Grundtvig’s copious use of images and symbols has given him the reputation of being an obscure and often incomprehensible writer. Only a few research students have ventured to approach Grundtvig on this side of his nature, whether it is a question of the exhaustive interpretation of particular works or of reading “ right through” his whole literary output for the purpose of establishing the underlying connections in his world of ideas and symbols. Dr. Helge Toldberg belongs to the latter group. In his book (the thesis for his Doctorate at the University of Copenhagen in 1950) he has undertaken the task of analysing the symbols employed by Grundtvig, in the belief that the frequent use of the same symbols by an author has a significance of its own, apart from the context in which they appear. The consequence of the acceptance of this principle by Dr. Toldberg is that in his study of Grundtvig’s writings the particular text is of minor interest; it is only in the comparatively few cases where the symbol constitutes its whole content that an analysis of any particular text is given. But, apart from this, the author’s method is the opposite of the genetical one. He is emphatically a systematiser and “ structuralist”, who works with clear concepts and wide ranges, and who embodies his results in definite schematic forms. In his book he attempts the immense task of finding his way down through the outward forms of Grundtvig’s literary output to its omnipresent foundation, its substratum, i. e., Grundtvig’s fundamental attitude to life or fundamental philosophy, and to the symbols employed by Grundtvig to express this fundamental philosophy. This substratum is determined by religious rather than by aesthetic factors, and Grundtvig’s choice of symbols is determined in great measure by this circumstance. Dr. Toldberg divides Grundtvig’s symbols into two groups: the symbols of life and faith which are closely connected with the substratum, and the legendary and traditional symbols taken from mythology and history which are more arbitrary and independent of the substratum. But even the last-named group of symbols is also strictly determined by the substratum, and the author’s division must therefore be regarded as a weakness ind the book and as serving an expository rather than a descriptive purpose. And indeed in practice he does not invariably keep to the sharp division he himself has made. Dr. Toldberg also makes use of the following fundamental concepts (borrowed from John Stuart M ill) : denotation, i. e., interpretation, direct signification, and connotation, i. e., connected or subsidiary ideas, the associative element. The principle of denotation is posited as the distinguishing mark of the poetry whose strength — as well as its limitations — lies in definite meanings of words, in classical clarity (typical author: Virgil). If a poem is rich in connotations, it may be characterised as romantic (in the wider sense); a poem of this kind aims first and foremost not at clarity but at plenitude (typical authors: Shakespeare, Grundtvig). Grundtvig, who despised Virgil and loved Shakespeare, is romantic in the sense that his symbolism points away from that which symbolises towards that which is symbolised (in contradistinction to that of the classical writers). Dr. Toldberg’s interpretation of Grundtvig is thus principally concerned with the subsidiary meanings which accompany the symbols, and here his philological and mythological scholarship achieves many triumphs. Thanks to an excellent index, the book can be used as a regular reference book for the interpretation of Grundtvig. The constant and the changing elements in the connotations are acutely observed, and where the symbols of life and faith are in question we are shown the coincidence between the changes in their connotations and the mutations in Grundtvig’s religious experience. The wide survey taken by Dr. Toldberg and his sense for the recurrent symbols as such can, however, cause him sometimes to overlook obvious connections and details within a particular text. From the point of view of pure literary scholarship his method can become dangerous in its denial of the organic microcosm of the particular work taken in isolation. But his system gives his grandly-conceived attempt at interpretation a firm structure which is admirable and instructive. However, the fact that the distinction between connotations and denotations may sometimes appear to be effaced raises a problem which the author has not recognised or discussed. Many of Grundtvig’s connotations really derive their character from what might be called “ private denotations” . A recognition of this problem could have given occasion for fruitful aesthetic and critical reflections. Does not a great deal of Grundtvig’s writing show traces of stiffening into a routine of conventional phraseology? And does not the recognition of this create the background for an even higher appreciation of his finest passages which reach the heights of inspiration? In the valuable chapters on Grundtvig’s symbolic language and symbolic vision (P. 37—72) two central concepts in Grundtvig’s writing are brought to light: “ spejl” = “mirror” (or “ spejling” = “mirroring”), and “ gaacfe” = “mystery” . Man (i. e. Grundtvig) must apprehend synthetically, not analytically. And the synthesis which must be apprehended everywhere is “ God’s purpose in the historical and mythological context” (P. 64). The world, history and human life mirror the Divine Being, and the poet’s work is to interpret this mirroring and nothing else. Thus Grundtvig regards science as being in subordination to faith, which must reject every scientific interpretation that is incompatible with this. (Grundtvig was therefore opposed to the astronomical theories of Copernicus.) For Grundtvig existence, history, and the origin of Christianity are a series of mysteries, which can only be solved with the help of the Christian faith. The task is the interpretation of visions, and this is only possible through adopting a prophetic standpoint in relation to present and past events (P. 68). Words like “wondrous” , “wonderful” and “ to illumine” are therefore favourite words for Grundtvig. Dr. Toldbergs book is written in an exact and technical scholarly language which makes it difficult for non-specialists, and indeed for specialists as well. There seems to be something tragic in the fact that while the book’s terminology and method are addressed to readers who may be regarded as being out of touch with Grundtvig’s world of ideas, its content is concerned in great measure with what is most centrally Grundtvigian! Dr. Toldberg has begun by discussing the symbols of life and faith, and has afterwards discussed the traditional historical and mythological symbols. To have discussed them in the reverse order would have been better, and would have led the reader in clearer fashion and along an ascending path into the centre of Grundtvig’s spiritual world. The long section about legendary and traditional symbols is the most imposing from the point of view of scholarship, with its wealth of observation and power of combination. But the deepest perspectives are to be found in the section about the symbols of life and faith. The notes with which the book is liberally provided contain a wealth of information and suggestions for further study.